Hysteresis and the European unemployment problem revisited - Galí, Jordi (Frankfurt am Main, 2015)
"The unemployment rate in the euro area appears to contain a significant nonstationary component, suggesting that some shocks have permanent effects on that variable. I explore possible sources of this nonstationarity through the lens of a New Keynesian model with unemployment, and assess their empirical relevance."